2020
DOI: 10.1002/chem.201905312
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics and Stereoselectivity of Chiral Benzylideneamine N,C‐Chelate Borane Photo–Thermal Isomerization

Abstract: New chiral N,C‐chelate organoboron compounds based on benzylideneamines (bza) with the general formula of B(bza‐R)Mes2 (R=H or Me; Mes=mesityl) are reported. A chiral substituent group R‐ or S‐CH(CH3)Ph (Ph=phenyl) was introduced to the imine center, which imposed a previously unobserved pseudo‐ or axial‐chirality on the BMes2, creating distinct diastereomers. NMR spectroscopic studies established that the diastereomers undergo slow exchange in solution at ambient temperature. The chiral N,C‐chelate B(bza‐R)Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…2 for assignment of the bond lengths and bond angles.bThe tetrahedral character of the dihedral angle (THC DA ) was calculated based on six angles around the boron atom using the equation in ref. 22.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 for assignment of the bond lengths and bond angles.bThe tetrahedral character of the dihedral angle (THC DA ) was calculated based on six angles around the boron atom using the equation in ref. 22.…”
Section: Resultsmentioning
confidence: 99%
“…13 Due to the high stability of the B-C bonds, BC 4 boranes exhibit high stereochemical stability. 14 To date, chiral tetrahedral boranes with B-N, [15][16][17][18][19][20][21][22][23][24][25][26][27] B-O, [28][29][30][31] B-H, 32,33 and boron-heteroatom [34][35][36][37] bonds have been synthesized and the stereochemistry of the compounds has been studied extensively. For example, Toyota has reported stable chiral tetrahedral boranes with three B-C bonds and one B-N bond (BC 3 N), and examined the racemization process (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this fascinating process, the rearranged "dark" products significantly limit their usability for real-life applications [30]. In order to control such process and to increase photochemical stability, several modifications (such as modulation of electronic factors and steric congestion) have been suggested [31,32]. It is shown that the functionalities attached to the chelating/auxiliary units significantly affect the isomerization process [33].…”
Section: -Arylpyridine-derived N^c-chelatesmentioning
confidence: 99%
“…A similar observation was made by Yam et al [37] Here, the authors merged photoactive diarylethene-functionalized N∧C chelated thienylpyridine with bisalkynyl borane complexes. In order to control such process and to increase photochemical stability, several modifications (such as modulation of electronic factors and steric congestion) have been suggested [31,32]. It is shown that the functionalities attached to the chelating/auxiliary units significantly affect the isomerization process [33].…”
Section: -Arylpyridine-derived N^c-chelatesmentioning
confidence: 99%
“…Thirdly the very recent enantioselective, catalytic creation of enantiomeric boron compounds 1 or ent ‐ 1 will be highlighted. Finally the chiroptical properties of enantiomerically pure boron complexes and their role as ‘’smart’ materials and devices will be presented [8] …”
Section: Introductionmentioning
confidence: 99%